2022
DOI: 10.1149/1945-7111/ac9edf
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of PEFC Performance Stability under High and Low Humidification Conditions by Use of a Gas Diffusion Layer with Interdigitated Gas Flow Channels

Abstract: A new design concept for polymer electrolyte fuel cells, which included a flat-metal separator and a gas diffusion layer (GDL) with interdigitated gas flow channels (FCs), was developed in our previous research. This design led to improved performance compared to that obtained with the conventional design of a metal separator with FCs and a flat GDL. Applications of the interdigitated gas flow channels formed on the separator, however, have conventionally faced two issues associated with low performance: one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We evaluated the PEFC performance of the PFSA composite PEMs membranes in a single cell FC using a MEA with an area of 1 cm 2 . Herein, the PFSA composite membrane (15 wt % thin fiber, 39 μm thick) with the highest proton conductivity and mechanical properties and pristine PFSA membrane (36 μm thick) were used. Figure shows the polarization curves of FCs using the PFSA composite and pristine PFSA membranes under three conditions.…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated the PEFC performance of the PFSA composite PEMs membranes in a single cell FC using a MEA with an area of 1 cm 2 . Herein, the PFSA composite membrane (15 wt % thin fiber, 39 μm thick) with the highest proton conductivity and mechanical properties and pristine PFSA membrane (36 μm thick) were used. Figure shows the polarization curves of FCs using the PFSA composite and pristine PFSA membranes under three conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have found that the mass transfer and water management of a fuel cell can be improved by changing the flow field structure in the bipolar plate, as shown in Figure 1 a . [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] For example, multi‐serpentine flow fields, [ 27 ] parallel flow fields, [ 28 ] cross‐type flow fields [ 29 ] and various bionic flow fields have been designed and prepared. [ 30 , 31 , 32 , 33 , 34 ] To further enhance the water management capability, some researchers have tried porous flow fields such as metal foam [ 35 , 36 ] or graphene foam.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Moreover, an integrated GDL with a structure that integrates flow field and GDL has shown good performance in enhancing the gas transfer performance and water management capabilities of fuel cells in Figure 1b . [ 9 , 25 , 26 , 35 , 39 ] However, This integrated GDL still has some disadvantages. First, the bottom of the common integrated GDL flow channel is relatively dense.…”
Section: Introductionmentioning
confidence: 99%